306 Involvement of toll-like receptor 4 in PCSK9-mediated biological effects in cell culture models. (8th December 2021) - Scalise, Valentina; Sanguinetti, Chiara; Lai, Michele; Neri, Tommaso; Celi, Alessandro; Pedrinelli, Roberto
Abstract: Aims: The link between pro-protein convertase subtilisin/kexin 9 (PCSK9) and inflammatory-related disease was supported in several experimental and human studies, which show how the protein could acts independent its canonical mechanism, by activation of inflammatory, apoptotic and immune pathways. Among these, TLR4/NFKB signalling pathway was found to be one of the main pathways mediating the PCSK9-induced increase of pro-inflammatory and pro-thrombotic molecules, such as TNF-alpha, IL-6, IL-1, MCP-1, and TF. To investigate the direct involvement of hTLR4 in recognition of exogenous human recombinant (hr) PCSK9. Methods: Experiments were carried out in three cell line: (i) HEK293-hTLR4-GFP cell lines obtained by stable co-transfection of HEK293 cells with the pUNO1-hTLR4-GFP, a plasmid expressing the hTLR4 gene fused to a GFP gene; (ii) HEK293-hTLR4 + cells obtained by co-transfection of hTLR4 receptor and its accessory proteins MD-2 and CD14, and an inducible secreted embryonic alkaline phosphatase (SEAP) reporter gene; (iii) HEK293-Null2 cells, a cell line lacking TLR4 expression, used as negative control. NFkB activity were measured by the SEAP reporter gene assay using a fluorescence detection method, while localization of hTLR4 and exogenous hrPCSK9 by confocal microscopy. Results: hrPCSK9 (1 µg/mL) activates NFkB in HEK293-hTLR4 + cells [SEAP activity-OD 620 nm: from a baseline of 0.18 ± 0.06 to 0.68 ± 0.05 ( N  = 8), P  < 0.001] to an extent comparable to Lipopolysaccharide (LPS), the specific agonist of TLR4. Colocalization of hrPCSK9 and TLR4s was clearly documented by quantitative confocal microscopy in HEK293-hTLR4-GFP cell line, that comprises the analysis of more than 80 fields in ∼2.10 5 cells/well and showing a percentage of co-localization of ∼4% in membrane spots ( P  < 0.01). Conclusions: Our data support the results reported in previous studies that attribute to PCSK9 a pathophysiological role in development of chronic inflammation and related-diseases such as atherothrombosis. A behaviour that extends far beyond LDLR degradation, via a mechanism that might be mediated at least in part by recognition of PCSK9 by the TLRs and later activation of NFKB intracellular pathway. Future studies will be important to better investigate the specific binding site engaged in the PCSK9-TLR interaction and to discriminate the intracellular transduction pathways involved in this response, in order to provide a theoretical basis for the development of innovative therapeutic strategies.